Metodologías para la reducción de xenofobia aplicadas en prácticas preprofesionales con comunidades juveniles venezolanas (Tema Central) - Suárez Pinzón, Janina Fernanda (2024)
This study analyzes methodologies for the reduction of xenophobia applied in pre-professional practices, mainly with Venezuelan youth communities, in the context of the actions implemented by the Universidad de las Artes de Guayaquil- Ecuador. Projects developed within the framework of subjects associated with community outreach are detailed, in which strategies based on participatory action research and with an inclusive approach are implemented, such as: Respiramos Inclusión and the School of Social and Community Leadership. These strategies enable actions in which students generate learning and contribute to the achieve-ment of their own creative processes. Among the main results of the methodology implemented, it should be noted that from 2019 to the present, the processes have been systematized in the publication of the book: ‘Pedagogies of the Arts and Humanities: Praxis, Research and Interculturality’. The transcendence of the projects described above can be seen in the ‘Oscar Arnulfo Romero’ Ibero-American Prize for Human Rights Education, where the project ‘Toolbox for non-formal education of the Network of Human Rights and Nature Defenders’ won the category B, NGOs, and civil society organizations.